Lateralization of music processing with noises in the auditory cortex: an fNIRS study - Santosa, Hendrik; Hong, Melissa Jiyoun; Hong, Keum-Shik (Frontiers in Behavioral Neuroscience, 2014)
The present study is to determine the effects of background noise on the hemispheric lateralization in music processing by exposing fourteen subjects to four different auditory environments: music segments only, noise segments only, music+noise segments, and the entire music interfered by noise segments. The hemodynamic responses in both hemispheres caused by the perception of music in 10 different conditions were measured using functional near-infrared spectroscopy. As a feature to distinguish stimulus-evoked hemodynamics, the difference between the mean and the minimum value of the hemodynamic response for a given stimulus was used. The right-hemispheric lateralization in music processing was about 75% (instead of continuous music, only music segments were heard). If the stimuli were only noises, the lateralization was about 65%. But, if the music was mixed with noises, the right-hemispheric lateralization has increased. Particularly, if the noise was a little bit lower than the music (i.e., music level 10 15%, noise level 10%), the entire subjects showed the right-hemispheric lateralization: This is due to the subjects’ effort to hear the music in the presence of noises. However, too much noise has reduced the subjects’ discerning efforts.